Antenna systems and electronic warfare applications - Poisel, Richard (Artech House, 2012)
Antenna systems play a critical role in modern electronic warfare communications and radar. This book serves as a one-stop resource for practical EW antenna system know-how. Supported with over 700 illustrations and nearly 1,700 equations, it offers professionals detailed explanations of the important foundations and aspects of this technology.